Human Anatomy: An Inlet of Medicine and Surgery - Abdelmonem, Awad Hegazy (International Journal of Human Anatomy, 2019)
An educational essay frames human anatomy as foundational to medicine and surgery, highlighting learning modalities and integration with imaging and simulation.
Keywords: Anatomy